Erfaringer med helsemonitorering for KOLS-pasienter - Bjørkquist, Catharina (Nordisk tidsskrift for helseforskning, 2015)
This article analyzes how health monitoring by tablet computer of COPD patients can contribute to safety and coping. The aim is to document and discuss experiences from users and the project team member who is also a nurse, with the use of telecare technology. The study was qualitative, using in-depth interview and short enquetes. Results show that the users increased their understanding of their physical condition and got better control of their illness. Accordingly, they coped better and felt more secure. Their level of activity was hardly affected even though one patient argued that the monitoring helped her adapt the level of activity to her present physical condition. Based on this study, we have, however, no significant indication that health monitoring by the use of tablet computer may reduce hospitalization and readmission rates.